The trouble with ‘truth’. On the politics of life and death in the assessment of queer asylum seekers - Lunau, Marie (Kvinder, Køn & Forskning, 2019)
This article explores death and dying in the context of queer migration by reflecting on the ways in which queer asylum seekers are exposed to various forms and manifestations of death through the process of seeking asylum. The article is based on qualitative interviews with queer asylum seekers in Denmark. Drawing on the concept of necropolitics, the article considers how the politics of truth within the asylum system manage life and death not only by the rejection and deportation of applicants, but also by exposing applicants to a slow death in the temporalities of a prolonged process of seeking asylum. The politics of truth within the asylum system appear to be predicated on ideals of normalised national white queerness and homonormativity that come to determine queer asylum seekers’ legitimacy and access to inclusion. Queer migrants’ paths to protection play out in a geopolitical context where the hope of life, asylum and citizenship are infused with deathly practices and normative imaginaries of truthful queerness.